Determinant factors of banking profitability: an application of quantile regression for panel data - Adriana Bruscato Bortoluzzo; Rodrigo Ricardo Ciganda; Mauricio Mesquita Bortoluzzo (Future Business Journal)
Abstract This study examines the determinants of bank profitability using a quantile regression approach, offering insights into factors affecting banks across different percentiles of profitability. Utilizing a comprehensive database from Orbis covering 1200 top-market institutions across 101 countries, the research uniquely employs dynamic panel quantile regression while addressing sample survival bias. Our findings highlight that bank size and capital adequacy negatively impact profitability, whereas market value exerts a positive influence on higher profitability banks. Credit risk affects profitability differently across levels of profitability, and inflation rate shows significance only for higher profitability banks. The study contributes to the existing literature by offering valuable insights into the factors determining bank profitability and how they behave at different percentiles in the sample, suggesting the importance of bank efficiency and competition in promoting economic growth.